WAYS TO REDUCE RISKS AFFECTING THE INCREASE OF ENTERPRISE INCOME (American Journal of Business Management, Economics and Banking, 2024)
In this article, the types of risks affecting the income of enterprises, the factors of their occurrence and different approaches to prevention are proposed. In addition, the concept of “revenue-factors-risk-revenue” impact has been developed to minimize the risks affecting the income of enterprises.